Tuning the resistive switching properties of TiO2-x films - Ghenzi, Néstor (2015)
We study the electrical characteristics of TiO2-x-based resistive switching devices fabricated with different oxygen/argon flow ratio during the oxide thin film sputtering deposition. Upon minute changes in this fabrication parameter, three qualitatively different device characteristics were accessed in the same system, namely, standard bipolar resistive switching, electroforming-free devices, and devices with multi-step breakdown. We propose that small variations in the oxygen/ argon flow ratio result in relevant changes of the oxygen vacancy concentration, which is the key parameter determining the resistive switching behavior. The coexistence of percolative or non-percolative conductive filaments is also discussed. Finally, the hypothesis is verified by means of the temperature dependence of the devices in low resistance state.